AN INCREASE IN THE STUDY OF SCIENCE THE INFLUENCE OF THE STYLE OF THE SHAPE AND MOTION OBJECTS USING THE MEDIA CARD AUGMENTED REALITY - Inge Nur Indah Sri Rejeki Ratna Ningsih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
Learning Natural Sciences in the Kepanjen II Elementary School Jombang District in class IV on the material Effect of Style on the shape and direction of motion of objects, experiencing problems in the form of the difficulty of understanding the material by students. From the results of the evaluation of learning shows that only 55% of 30 students scored above the specified KKM of 75.0. Based on problems occur, the researchers planned improvement of learning 2 cycles.At the planning stage the analysis is done by KI and KD making indicators and learning objectives continued Developing learning implementation plans and Developing learning assessment instruments and making learning media namely Augmented reality applications. At the Implementation stage of learning has increased both the activities of teachers and student activities. Overall the increase in teacher activity increased from 70% to 80%. Medium student activity increased from 72% to 90%. Learning outcomes before using the media card Augmented Reality 55% completeness classic. Student learning outcomes in classical learning cycle completeness 63% and cycle II increased to 84%